1996
DOI: 10.2307/282017
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake-Induced Subsidence and Burial of Late Holocene Archaeological Sites, Northern Oregon Coast

Abstract: Fire hearths associated with prehistoric Native American occupation lie within the youngest buried lowland soil of the estuaries along the Salmon and Nehalem rivers on the northern Oregon coast. This buried soil is the result of sudden subsidence induced by a great earthquake about 300 years ago along the Cascadia subduction zone, which extends offshore along the North Pacific Coast from Vancouver Island to northern California. The earthquake 300 years ago was the latest in a series of subsidence events along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…In the silty clay, foraminifera produced estimates of paleomarsh elevations between 0.70 m and 1.16 m MSL, which all have good matching analogues. The post-seismic (E post ) elevation from the sample (0.38 m depth) immediately above the tsunami sand (Briggs, 1994;Nelson et al, 1998) is 0.70 m ± 0.18 m. The minimum coseismic subsidence is 0.85 m. Grant (1994) and Minor and Grant (1996) suggested that Nehalem River experienced a change from a spruce forest to a Triglochin maritima colonized mudflat, producing 1 m to 2 m coseismic subsidence.…”
Section: South Sloughmentioning
confidence: 99%
See 4 more Smart Citations
“…In the silty clay, foraminifera produced estimates of paleomarsh elevations between 0.70 m and 1.16 m MSL, which all have good matching analogues. The post-seismic (E post ) elevation from the sample (0.38 m depth) immediately above the tsunami sand (Briggs, 1994;Nelson et al, 1998) is 0.70 m ± 0.18 m. The minimum coseismic subsidence is 0.85 m. Grant (1994) and Minor and Grant (1996) suggested that Nehalem River experienced a change from a spruce forest to a Triglochin maritima colonized mudflat, producing 1 m to 2 m coseismic subsidence.…”
Section: South Sloughmentioning
confidence: 99%
“…Grant (1994) and Minor and Grant (1996) found widespread stratigraphic and plant macrofossil evidence of subsidence during the AD 1700 earthquake exposed in bank sections over much of the lower estuary that traces landward for hundreds of meters. A sharp upper contact between the buried peaty horizon, including Native American fire hearths (Woodward, 1990), and an overlying muddy or sandy unit infer sudden subsidence during a megathrust earthquake (Grant, 1994;Minor and Grant, 1996). The mean age of eight radiocarbon-dated herbs rooted in the top of the buried peaty horizon at the outcrop at this site is AD 1666-1950 (179±15 14 C yrs BP; Nelson et al, 1995).…”
Section: Stratigraphy Of the Ad 1700 Earthquake At Five Estuariesmentioning
confidence: 99%
See 3 more Smart Citations